Variability and recent trends in the African terrestrial carbon balance - P. Ciais; S.-L. Piao; P. Cadule; P. Friedlingstein; A. Chédin (Biogeosciences, 2009)
We modeled the African terrestrial carbon balance over the past century using a spatially resolved process based vegetation model (ORCHIDEE). The model is forced by changing climate and by human-induced changes in land use. It includes a simple parameterization of natural fires, but the natural vegetation dynamics was ignored. The period analyzed is 1901–2002. Overall, we found that the African net terrestrial carbon balance (Net Biome Productivity, NBP) increased from a net CO2 source to the atmosphere of 0.14 Pg C yr−1 in the 1980s to a net sink of 0.15 Pg C yr−1 in the 1990s. The land use flux alone is estimated to be a source of 0.13 Pg C yr−1 caused by deforestation. This implies that climatic trends (mainly increasing precipitation) and CO2 increase (fertilization effect), are causing a sink of 0.28 Pg C yr−1 which offsets the land-use source. We found that the interannual variability of NBP is large, and mostly driven by photosynthesis variability. Over savannas, photosynthesis changes from one year to the next are strongly correlated with rainfall changes (R2=0.77 in northern Africa, and R2=0.42 in southern African savannas). Over forests, such a control by rainfall is not found. The main spatial pattern of interannual variability in NBP and photosynthesis/ecosystem respiration fluxes is related with ENSO, with dryer conditions prevailing over savannas during El Niño and wetter conditions over forests. Climate induced variations in fire emissions respond to this ENSO forcing, but do not determine strongly the NBP interannual variability. Finally, we model that ecosystem respiration variations (mostly autotrophic respiration) are correlated with those of photosynthesis, on interannual as well as on decadal time scales, but this result is uncertain given the potential for acclimation for autotrophic respiration processes.